LINGUISTIK FUNGSIONAL : DIMENSI DALAM BAHASA - Bahagia Saragih (BAHAS, 2016)
This article deals with the explanation about a small part of the study of Systemic Functional Linguistics (SFG), i.e. dimension in language. Systemic Functional (SF) theory views language as a social semiotic a resource people use to accomplish their purposes by expressing meanings in context. Language is a systematic resource for expressing meaning in context and linguistics, the study of how people exchange meanings through the use of language. This view of language as a system for meaning potential implies that language is not a well defined system not a "the set of all grammatical sentences." It also implies that language exists and therefore must be studied in contexts such as professional settings, classrooms, and language tests. In short, SF theory states that particular aspects of a given context (such as the topics discussed, the language users and the medium of communication) define the meanings likely to be expressed and the language likely to be used to express those meanings.   Kata Kunci : Systemic Functional Linguistics (SFG), grammatical sentences.